KNOWLEDGE OF UNDERGRADUATE NURSING STUDENTS ABOUT GENERAL WOUND CARE: OBSERVATIONAL STUDY (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To identify nursing students’ knowledge about general wound care. Methods: This is an observational-descriptive research conducted with final-year nursing undergraduate students from higher education institutions in the Cariri region, Ceara, Brazil. Data collection was developed through the sampling technique snowball or snowball sampling. The data were tabulated in Microsoft Excel Spreadsheet and later analyzed by simple descriptive statistics. Results: The sample included 211 nursing students, from the ninth (123) and tenth (88) semester, from public (50) and private (161) institutions. Among the students, 122 highlighted professors and scientific events as sources of searching for primary information about wounds, and that in their hospital internships they have skin assessment as part of the activities they perform (85.8%). About the knowledge, the data that showed the highest percentage are regarding aspects of wound assessment (98.6%), coverage (96.7%) and biological factors of healing (92.4%). The participants left to be desired in aspects of PU prevention (39.8%) and Braden scale, with 45% of correct answers. Conclusion: This study made it possible to identify the general knowledge about wounds of graduating nursing students.